(untitled) (SYNAPSES: INSIGHTS ACROSS THE DISCIPLINES, 2025)
Alcoholic liver cirrhosis (ALC), a severe consequence of chronic alcohol consumption, exhibits distinct pathomorphological changes influenced by age, impacting disease progression and therapeutic outcomes. This article investigates age- related variations in the histopathological and morphometric features of ALC, focusing on fibrosis severity, hepatocyte degeneration, and inflammatory patterns across different age groups. The study analyzes liver biopsy and autopsy samples from 300 ALC patients, revealing advanced fibrosis (stage F4) in 70% of patients aged >50 years versus 50% in those <50 years (p < 0.01). Globally, ALC affects 4.5 million individuals, contributing to 370,000 deaths annually, with a 2-fold higher mortality risk in older patients (OR = 2.1, 95% CI: 1.6–2.8, p < 0.001). This study aims to enhance diagnostic precision, inform age- tailored therapies, and address disparities in ALC management, particularly in regions like Uzbekistan with rising alcohol-related liver disease.